PENGARUH MEDIA PEMBELAJARAN AUGMENTED REALITY TERHADAP ASPEK KOGNITIF SISWA KELAS V DALAM MATERI ANATOMI - Pebriyani, Putri; Ismail, Ali; Lichteria Panjaitan, Regina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study is titled “The Effect of Augmented Reality-Based Learning Media on the Cognitive Aspects of Fifth Grade Students in Anatomy Material.” It aims to determine the effect of using AR media on students’ cognitive learning outcomes in respiratory and digestive system topics. The research employed a quasi-experimental method with a pretest-posttest control group design. The subjects consisted of 60 fifth-grade students from SDN Pamujaan 01, divided into an experimental class and a control class. Data were collected through pretest and posttest assessments, and analyzed using several techniques including normality test, homogeneity test, hypothesis test, N-gain test, and effect size analysis. The results showed that AR media had an effect on students’ science learning outcomes. Therefore, it can be concluded that AR media has a positive and significant impact on enhancing students’ cognitive aspects and can serve as an innovative alternative in teaching abstract anatomical concepts.